2002
DOI: 10.1192/pb.26.8.295
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment rates among patients with long-term mental health problems

Abstract: Aims and MethodTo examine the vocational status of people with longer-term mental health problems in the inner London Borough of Wandsworth. Data collected over 10 years on 1 April each year as part of an annual census of adults with longer-term mental health problems using community mental health and rehabilitation teams were analysed to examine the vocational status of these groups.ResultsWithin the borough unemployment rates among people with longer-term mental health problems increased steadily during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
2
8

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 6 publications
(8 reference statements)
4
65
2
8
Order By: Relevance
“…Poor employment outcomes are a constant finding in research on first-episode psychosis (e.g. Mason et al, 1995;Gupta et al, 1997;Singh et al, 2000), with employment rates for people with longer-term schizophrenia reported to be as low as 4% (Perkins & Rinaldi, 2002). O'Brien et al (2003), in their study of the effects of training clinical staff in the practice of evidence-based supported employment without a vocational worker integrated into the team, found that only 6% of people achieved open employment Rinaldi et al Supported employment in first-episode psychosis original papers thereafter, which compares with a figure of 11% found in a naturalistic study following people in a vocational rehabilitation programme (Reker et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor employment outcomes are a constant finding in research on first-episode psychosis (e.g. Mason et al, 1995;Gupta et al, 1997;Singh et al, 2000), with employment rates for people with longer-term schizophrenia reported to be as low as 4% (Perkins & Rinaldi, 2002). O'Brien et al (2003), in their study of the effects of training clinical staff in the practice of evidence-based supported employment without a vocational worker integrated into the team, found that only 6% of people achieved open employment Rinaldi et al Supported employment in first-episode psychosis original papers thereafter, which compares with a figure of 11% found in a naturalistic study following people in a vocational rehabilitation programme (Reker et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the intervention, just under two-thirds the patients (n=27) were not engaged in any sort of work or education. Only 4 (10%) were Rinaldi et al Supported employment in first-episode psychosis original papers (55) 3 (7) 1 (5) engaged in open employment -a figure similar to that for the whole population of longer-term service users (Perkins & Rinaldi, 2002). Following vocational profiling, and input from the vocational specialist and the team, there was a significant increase in the proportion of patients engaged in work or educational activity by 6 months (w 2 =28.4, d.f.=12; P50.005).…”
Section: Model Fidelitymentioning
confidence: 99%
“…For many participants volunteering is disconnected from their paid work. As others have argued, rather than being a route into work volunteering may act more as an alternative to work, or as additional to work (Corden and Ellis, 2004;Hardill and Baines, 2008;IVR, 2004;Perkins and Rinaldi, 2002). Indeed, treating volunteering as work is only one way to conceptualise it: it can also be conceptualised as a: leisure, service, or caring activity (Rochester et al, 2010).…”
Section: Volunteering Is About More Than Employabilitymentioning
confidence: 99%
“…133 While some aspects of employment can be stressful for some individuals, a 10-year study found that being in steady employment was significantly associated with a reduction in mental health service use over this time period. 134 However, individuals with SMI are much less likely to be employed than the general population, 135 and face a variety of barriers to gaining employment such as poor functioning due to illness 136 as well as stigma in the form of negative employer attitudes. 137 Furthermore, while we undoubtedly need to increase the level of employment for those with SMI, for some individuals certain forms of employment may be unobtainable.…”
Section: Meaningful Activitiesmentioning
confidence: 99%